Effect of Yucca schidigera supplementation in diet on the health performances, blood biomarkers, and relative telomere length of broiler chickens reared under tropical conditions - Abu Kassim, Nafeesa; Lim, Eric Teik Chung; Alghirani, Mohamed M.; Yee, Lyn Ong; Kamalludin, Mamat Hamidi; Abdullah Jesse, Faez Firdaus; Teck, Chwen Loh (Gorgan University of Agricultural Sciences and Natural Resources, 2023)
The main aim of this study was to elucidate the potential of Yucca schidigera supplementation on the health performances, blood biomarkers, and relative telomere length of broilers reared under tropical conditions. A total of 300 one-day-old male Ross 308 broilers were purchased, weighed, and divided randomly into six dietary regimens. The dietary treatments consisted of T1: commercial feed without antibiotics (negative control) and T2: commercial feed added with 100 mg/kg oxytetracycline (positive control). Birds in T3, T4, T5, and T6 were fed with commercial feed supplemented with 25, 50, 75, and 100 mg/kg of powdered Y. schidigera saponins. The broilers were monitored daily and the clinical sign and mortality were recorded. On day 42, ten male broilers from each treatment were randomly selected and slaughtered, and blood samples were collected for leucocyte profiling, immunoglobulins, cytokines, and telomere length analyses. All data obtained were subjected to the Chi-Square Test, one-way analysis of variance (ANOVA), and Tukey Post-Hoc Test to determine the significant differences among treatment groups. The data were considered significant at P < 0.05. Throughout the 42-day study, a few cases of leg problems, diarrhea, and mortality were observed, but there were no significant associations (P > 0.05). However, there were significant differences (P < 0.05) in the leucocyte profiling, immunoglobulins, cytokines, and telomere length expression among treatments. Negative control broilers not fed with any additive demonstrated the lowest values as compared to the antibiotic and treatment groups. Overall, T6 broilers fed with a diet supplemented with 100 mg/kg of Y. schidigera saponins exhibited the best leucocyte profiling (increased total WBC count, monocytes, and basophil count; decreased H/L ratio), immunoglobulins (upregulated Ig-G, Ig-A, and Ig-M,), cytokines (increased IL-4 and IL-7), and the longest telomere length expression followed by T2 broilers. In summary, this study has established that 100 mg/kg of Y. schidigera saponins supplementation in diet can be used to enhance the health performances of broilers raised under hot and humid conditions.